Development of discontinuous fibre preforming processes - Patel, Critesh (2013)
Discontinuous fibre composites are under increasing investigation for structural and semi-structural components as they are easily automated, making it possible to remove costly hand labour based steps typically associated with advanced fibre reinforced composites. Directed fibre preforming (DFP) is one possible process which has several advantages when compared with competing techniques. Low material and process costs coupled with short cycle times means the process is suited to medium volume production (typically <10,000 ppa). Predicting mechanical performance remains a major obstacle to industrial adoption however, due to the stochastic nature of fibre distribution. This is of particular importance for structural applications where minimum property requirements and a greater certainty of performance must be achieved.